Identifikasi Penurunan Tekanan Darah Pasien Hipertensi melalui Pemanfaatan Terapi Jus Citrullus Lanatus dalam Mendukung Pola Hidup Sehat - Dotulong, Fransiskus Xaverius; Rembet, Ignatia Yohana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Hypertension is a non-communicable disease with a relatively high mortality rate, often referred to as a “silent killer” because it poses a risk of triggering various life-threatening complications. Hypertension management can be conducted by nurses through non-pharmacological interventions; however, such measures are still infrequently applied. The use of Citrullus lanatus (watermelon) juice represents a non-pharmacological therapy that may help control elevated blood pressure. This study aims to analyze the effect of Citrullus lanatus juice therapy on blood pressure reduction among hypertensive patients. This quantitative research employed a quasi-experimental design with a pre-test–post-test control group. The sampling technique used non-probability purposive sampling based on inclusion and exclusion criteria and rule-of-thumb calculations. A total of 58 hypertensive patients in the working area of Ratahan Public Health Center participated (intervention group n = 44, control group n = 14). Blood pressure categories were determined using JNC VIII recommendations. Intervention group received 500 ml of watermelon juice, three times daily, for seven consecutive days, along with healthy lifestyle education. The Wilcoxon test showed a significant difference in the intervention group (p = 0.000 < 0.05), indicating a meaningful reduction in pre- and post-test blood pressure. In contrast, the control group showed no significant difference (p = 0.083 > 0.05). This study confirms that Citrullus lanatus juice is effective as a supportive non-pharmacological therapy for lowering blood pressure in hypertensive patients. Citrullus lanatus juice may be considered a complementary therapy that is accessible, affordable, and safe to support healthy lifestyle among individuals with hypertension.